The chambermaid [videorecording (DVD)] - Haeb, Ingo, 1970-; Krieps, Vicky, 1983-; Lauzemis, Lena, 1983-; Münster, Steffen; Orths, Markus, 1969- (Film Movement series, 2015)
Lynn is the most thorough chambermaid at the hotel where she works, leaving no shelf undusted, no sheet untucked. Fascinated by the lives of the guests she cleans up after and crippled by her own shyness, she rummages through their belongings and even hides under their beds, vicariously experiencing their conversations, meals and discreet interludes. When she finds herself present during a guest's S&M session with the call girl Chiara, Lynn can't help but let her curiosity get the better of her, clandestinely noting Chiara's phone number when the coast is clear. Bold and unrestrained, Chiara soon draws Lynn out of her shell, opening her up to a new intimacy Lynn had previously only experienced as an intrepid voyeur.